2019
DOI: 10.3390/polym11091401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibers Configuration and Thickness on Tensile Behavior of GFRP Laminates Exposed to Harsh Environment

Abstract: The present study indicates the importance of using glass fiber reinforced polymer (GFRP) laminates with appropriate thickness and fibers orientation when exposed to harsh environmental conditions. The effect of different environmental conditions on tensile properties of different GFRP laminates is investigated. Laminates were exposed to three environmental conditions: (1) Freeze/thaw cycles without the presence of moisture, (2) freeze/thaw cycles with the presence of moisture and (3) UV radiation and water va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…As a result, specimens whose fatigue lifetime results were analyzed to assess the mean value had dimensions l = 200 mm, w = 25 mm, and h = 1.16 mm. The effect of fiber configuration on the tensile behavior of similar material configurations was presented and widely discussed in the recent paper by Bazli et al [16]. In the literature [13] that was used in the process of data acquisition for calculations, it may be found that the basic static strength parameters of such material are:…”
Section: Materials Glarementioning
confidence: 99%
“…As a result, specimens whose fatigue lifetime results were analyzed to assess the mean value had dimensions l = 200 mm, w = 25 mm, and h = 1.16 mm. The effect of fiber configuration on the tensile behavior of similar material configurations was presented and widely discussed in the recent paper by Bazli et al [16]. In the literature [13] that was used in the process of data acquisition for calculations, it may be found that the basic static strength parameters of such material are:…”
Section: Materials Glarementioning
confidence: 99%
“…Despite the outstanding characteristics of FRP/PVC composites, their durability under harsh environmental conditions is still a serious concern [117]. There are numerous studies available on the short-term and long-term durability of different FRP/PVC composites as the main element and reinforcing members under various environmental conditions [95,[118][119][120][121][122]. In this regard, previous studies conducted on the durability of the mechanical properties of FRP composites under alkaline environment (i.e.…”
Section: Durabilitymentioning
confidence: 99%
“…They are used in many industries for different complex structures, such as aircraft, automobile, marine, and sports. Polymer matrix composites (CFRP and GFRP) are widely used composite materials [ 4 , 5 , 6 ]. Different manufacturing processes are used to fabricate composite parts like hand layup, autoclave, out-of-autoclave (OoA), and additive manufacturing (AM) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%